Photon radiation effects in kinematic reconstruction of top quarks. (1st December 2021) - Dobur, D.; Knolle, J.; Mestdach, G.; Skovpen, K.
Abstract: Kinematic reconstruction of top quarks allows to define a set of kinematic observables relevant to various physics processes that involve top quarks and provides an additional handle for the suppression of background events. Radiation of photons in association with the top quarks alters the kinematics and the topology of the event, leading to visible systematic effects in measurable observables. The present study introduces an improved reconstruction of the top quark kinematics in the presence of photon radiation. The results are presented for processes with top quark pair production, as well as for singly-produced top quarks.